The Impact of Speaking Anxiety on Third-Semester English Education Students’ Oral Performance at Tadulako University - Widya Pratiwi; Mukrim Mukrim; Maf’ulah Maf’ulah; Abd. Kamarrudin (MASI Mandiri Edukasi, 2026)
Speaking anxiety is a common psychological barrier that affects students’ ability to communicate effectively in English as a Foreign Language (EFL) contexts, where many students experience nervousness, lack of confidence, and fear of making mistakes during speaking activities, which may influence their oral performance. This study aims to explore how speaking anxiety affects the oral performance of third-semester English Education students at Tadulako University. This study employed a qualitative case study design involving five participants selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, reflection sheets, and document analysis, and analyzed using thematic analysis. The findings reveal that speaking anxiety manifests in emotional responses such as nervousness and fear, as well as behavioral signs such as hesitation, avoidance, and limited participation, and it also affects students’ fluency, coherence, and clarity of expression. Despite achieving high academic scores, students still experienced anxiety, indicating that psychological factors are not always reflected in performance outcomes. This study concludes that speaking anxiety significantly influences students’ oral performance and highlights the importance of supportive classroom practices to reduce its impact.